PROFIL PENDERITA GASTRO ESOPHAGEAL REFLUX DISEASE (GERD) DAN NON-EROSIVE REFLUX DISEASE (NERD) DI RSUD DR. SOETOMO SURABAYA - Irvinia Septarizka Putri Radjamin; Iswan Abbas Nusi; Viskasari Pintoko Kalanjati (Majalah Biomorfologi, 2019)
Background: Gastro Esophageal Reflux Disease (GERD) is a condition when food that had been ingested moves back up from the stomach to the esophagus periodically, causing heartburn. GERD cases that are followed up by esophagogastroduodenoscopy (EGD) can be diagnosed as Non-Erosive Reflux Disease (NERD) if there are no findings of mucosal damage at the esophagus. Objective: The objective is to study the overall prevalence of GERD and NERD patients on January until December of 2015, categorizing them according to age groups, gender, grade of esophageal mucosal damage according to Los Angeles grading, and also other EGD findings. Material and method: This is a descriptive research using secondary data collected from patients' medical record. Patients that are diagnosed as GERD or NERD are included as sample. Data are collected and processed by Microsoft Office Excel 2007. Result: A total of 122 medical records were collected, with 116 GERD patients and 6 NERD patients. There was increase of prevalence of GERD patients shown following the increase of age groups, while prevalence of NERD patients between age groups fluctuate. Both GERD and NERD patients are dominated by women, that is 62 patients (53.4%) and 5 patients (83.3%) respectively, compared to male, that is 54 GERD patients and 1 NERD patient. According to Los Angeles grading, the patients are mostly categorized as grade A (14.7%). However, there were 88 unclassified cases found so the result arguably needed a bigger sample and/ or data written in the medical record might not be clearly stated. The most dominant EGD finding in GERD patients was erosive gastritis (24.8%). Conclusion: There were 95% GERD patients and 5% NERD patients discovered in this study. The profile of GERD patients in this case was dominantly found in the age group of more than 50 years old, women, grade A, and with erosive gastritis in the EGD findings. The profile of NERD patients was not specific to a certain age group, but mostly found in women.